2009
DOI: 10.1523/jneurosci.5687-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Alterations of Corticostriatal Activity in the YAC128 Mouse Model of Huntington Disease

Abstract: Huntington disease is a genetic neurodegenerative disorder that produces motor, neuropsychiatric, and cognitive deficits and is caused by an abnormal expansion of the CAG tract in the huntingtin (htt) gene. In humans, mutated htt induces a preferential loss of medium spiny neurons in the striatum and, to a lesser extent, a loss of cortical neurons as the disease progresses. The mechanisms causing these degenerative changes remain unclear, but they may involve synaptic dysregulation. We examined the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
167
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(187 citation statements)
references
References 67 publications
17
167
0
Order By: Relevance
“…S3A; WT, n = 7; YAC128, n = 9; t test, P < 0.05), an effect that could also increase excitability of YAC128 SPNs at this age. Consistent with previous reports in other HD models (8,12,14), this early alteration of EPSCs was reversed in older animals. Thus, in SPNs recorded in slices from 5-to 6-mo-old YAC128 mice, there was a significant decrease in peak amplitudes of eEPSCs compared with SPNs from WT mice [ Fig.…”
Section: Significancesupporting
confidence: 92%
See 3 more Smart Citations
“…S3A; WT, n = 7; YAC128, n = 9; t test, P < 0.05), an effect that could also increase excitability of YAC128 SPNs at this age. Consistent with previous reports in other HD models (8,12,14), this early alteration of EPSCs was reversed in older animals. Thus, in SPNs recorded in slices from 5-to 6-mo-old YAC128 mice, there was a significant decrease in peak amplitudes of eEPSCs compared with SPNs from WT mice [ Fig.…”
Section: Significancesupporting
confidence: 92%
“…Due to its pivotal importance in these domains, changes in striatal physiology can contribute to multiple neurological diseases, including Huntington's disease, Parkinson's disease, dystonia, and others. An increasing number of reports suggest that changes in striatal synaptic physiology, including changes at glutamatergic, dopaminergic, and cholinergic synapses, are evident beginning in the prediagnostic phase of HD (5,6,(8)(9)(10)(11)(12)(13)(14)(35)(36)(37). These changes may contribute to early motor, cognitive, and psychiatric abnormalities, and could set the stage for the extensive pathophysiological alterations appearing later in the striatum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we are aware of no study in R6/1 mice, an in vitro intracellular recording study in R6/2 mice once again showed that their striatal MSNs were hyperexcitable at a presymptomatic age (6 wk), consistent with data from Rebec's group (22,23), and became hypoexcitable later at a symptomatic age (12 wk) (16). Another study of YAC128 transgenic mice also reported biphasic increase and subsequent decrease of synaptic transmission in the corticostriatal pathway with disease progression (24). Therefore, this age-related biphasic temporal evolution of basal ganglia physiology caused by mutant proteins might explain the discrepancy between the excitability observed in previous in vivo recording studies in presymptomatic R6/2 mice (6-9 wk) and our findings in older R6/1 mice (14-20 wk).…”
Section: Discussionsupporting
confidence: 58%